Novel cell culture system for monitoring cells during continuous and variable negative‐pressure wound therapy. Issue 1 (25th December 2022) - Yamashiro, Toshifumi; Kushibiki, Toshihiro; Mayumi, Yoshine; Tsuchiya, Masato; Ishihara, Miya; Azuma, Ryuichi
Abstract: Background: Although the clinical efficacy of negative‐pressure wound therapy (NPWT) is well known, many of its molecular biological mechanisms remain unresolved, mainly due to the difficulty and paucity of relevant in vitro studies. We attempted to develop an in vitro cell culture system capable of real‐time monitoring of cells during NPWT treatment. Materials and methods: A novel negative‐pressure cell culture system was developed by combining an inverted microscope, a stage‐top incubator, a sealed metal chamber for cell culture, and an NPWT treatment device. Human keratinocytes, PSVK‐1, were divided into ambient pressure (AP), continuous negative‐pressure (NPc), and intermittent negative‐pressure (NPi) groups and cultured for 24 h with scratch assay using our real‐time monitoring system and device. Pressure inside the device, medium evaporation rate, and the residual wound area were compared across the groups. Results: Pressure in the device was maintained at almost the same value as set in all groups. Medium evaporation rate was significantly higher in the NPi group than in the other two groups; however, it had negligible effect on cell culture. Residual wound area after 9 h evaluated by the scratch assay was significantly smaller in the NPc and NPi groups than in the AP group. Conclusion: We developed a negative‐pressure cell culture device that enables negative‐pressure cell culture under conditions similar to those used in clinical practice and is able to monitor cells under NPWT. Further experiments using this device would provide high‐quality molecular biological evidence for NPWT.